Motion monitoring system for the elderly - Lim, Sylvia (2018)
Falls are the leading cause of unintentional death amongst the elderly. With an increasing percentage of elderly living alone in their own homes, it is necessary to introduce measures that prevent falls from going unnoticed for a prolonged period of time. In this Final Year Project (FYP), a fall detection device will be designed using Raspberry Pi. It will detect the motion of the user using accelerometer and gyroscope. On top of the device designing, analysis and comparisons of the difference in parameters between certain common daily activities and falls will be carried out. This is to reduce the number of false alarms being sent out by the device. Being programmed on the Raspberry Pi also suggests the many possible extensions of this device since it is capable of running various Python scripts concurrently to achieve several objectives.